TRADISI MAGERET PANDAN SEBAGAI INSPIRASI PEMBELAJARAN MENDALAM DAN PENGUATAN KETERAMPILAN ABAD KE-21 - Harum Sunya Iswara; Pande Putu Yogi Arista Pratama (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aimed to explore the educational values embedded in the Mageret Pandan tradition of Tenganan Pegringsingan Village, Bali, and its relevance to deep learning and 21st-century skills enhancement in elementary education. Employing a qualitative descriptive-ethnopedagogy approach, data were collected through observation, in-depth interviews with traditional leaders, participants, and teachers, as well as documentation during the Ngusaba Sambah ceremony. The findings revealed that the Mageret Pandan tradition embodies moral and educational values such as courage, self-control, sportsmanship, and social solidarity, which can be transformed into contextual learning resources. These values align with the principles of deep learning: mindful, meaningful, and joyful, while simultaneously fostering the 4Cs of 21st-century skills: critical thinking, creativity, collaboration, and communication. Post-ritual practices such as mecane, meboreh, and megibung strengthen reflective, empathic, and cooperative learning experiences. Thus, the Mageret Pandan tradition provides an integrative cultural model for implementing deep learning in primary education, bridging local wisdom with global educational competencies.